MATHEMATICAL CONTENT KNOWLEDGE CALON GURU MATEMATIKA BERDASARKAN DIMENSI PENGETAHUAN TAKSONOMI BLOOM REVISI - Purnama Putra, Yuda; Amanda Puri, Fiki; Suciawati, Vici; Dede Anggiana, Agus (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2025)
Teachers play a central role in determining the success of the educational process, especially in mathematics learning, which requires a deep understanding of the subject matter. A professional mathematics teacher is expected to possess adequate Mathematical Content Knowledge (MCK) to deliver the material effectively. Therefore, prospective teachers need to be equipped not only with pedagogical skills but also with strong content mastery. This level of knowledge can be analyzed through the dimensions of the Revised Bloom’s Taxonomy, which includes factual, conceptual, procedural, and metacognitive knowledge. This study aims to identify the Mathematical Content Knowledge abilities of prospective mathematics teachers based on the Revised Bloom’s Taxonomy. The research used a quantitative method. The population consisted of seventh-semester students in the Mathematics Education (Tadris Matematika) Program at the Faculty of Tarbiyah and Teacher Training, IAIN Syekh Nurjati Cirebon. A total of 44 students were selected using cluster random sampling. Data collection techniques included non-test (questionnaire/self-report) and test (written questions). Data analysis involved data presentation, normality testing, and difference testing.The results showed that the Mathematical Content Knowledge of prospective mathematics teachers based on the knowledge dimensions of the Revised Bloom’s Taxonomy was consistent between test results and questionnaires. The highest level of MCK was found in the procedural knowledge dimension with a percentage of 27.12% based on the test results. There were no significant differences between male and female participants. Keywords: Mathematical Content Knowledge, Prospective Teachers, Revised Bloom’s Taxonomy